2007
DOI: 10.1093/hmg/ddm216
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based bioinformatic prediction and QUASEP identify genomic imprinting of the KCNK9 potassium channel gene in mouse and human

Abstract: Genomic imprinting is the epigenetic marking of gene subsets resulting in monoallelic or predominant expression of one of the two parental alleles according to their parental origin. We describe the systematic experimental verification of a prioritized 16 candidate imprinted gene set predicted by sequence-based bioinformatic analyses. We used Quantification of Allele-Specific Expression by Pyrosequencing (QUASEP) and discovered maternal-specific imprinted expression of the Kcnk9 gene as well as strain-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 35 publications
(50 reference statements)
5
53
0
Order By: Relevance
“…The Peg13 DMR also had a very clear CTCF peak in the paternal allele. Kcnk9 is maternally expressed in 11.5-dpc embryos and in adult brain (79), and Trappc9 exhibits imprinted expression in the neonatal brain (101). Kcnk9 and Trappc9 were not differentially expressed in MatDup.dist7 versus PatDup.dist7 MEFs, and this was in agreement with the absence of an allele-specific chromatin pattern.…”
Section: Downloaded Fromsupporting
confidence: 75%
See 3 more Smart Citations
“…The Peg13 DMR also had a very clear CTCF peak in the paternal allele. Kcnk9 is maternally expressed in 11.5-dpc embryos and in adult brain (79), and Trappc9 exhibits imprinted expression in the neonatal brain (101). Kcnk9 and Trappc9 were not differentially expressed in MatDup.dist7 versus PatDup.dist7 MEFs, and this was in agreement with the absence of an allele-specific chromatin pattern.…”
Section: Downloaded Fromsupporting
confidence: 75%
“…Recently, large-scale studies aimed at detecting novel imprinted genes (73). The predictions were based on RNA expression differences (1,28,57,83,101), DNA sequence-based computational predictions (50,51,79), DNA methylation differences (35,89), and epigenetic signature (8,18,54,56,103). The chromatin-based studies successfully predicted and identified novel imprinted genes but with variable specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, computational prediction of imprinted genes using DNA sequence features alone has been used for both the mouse and the human genomes. Data from these studies resulted in experimental validation of three imprinted genes in the mouse genome, and two candidate genes from analysis of the human genome may also be imprinted (26,36,37,50). However, data from reciprocal crosses are not available for the two genes reported to be imprinted in humans, which is essential to distinguish imprinted genes from expression quantitative trait loci (eQTLs).…”
mentioning
confidence: 99%